HOW DOES HALAL TOURISM CONTRIBUTE TO COMMUNITY ECONOMY? THE CASES OF TSUNAMI MUSEUM AND THE PLTD FLOATING SHIP IN BANDA ACEH, INDONESIA - Afriwanda Afriwanda; Sofyan Syahnur; Eddy Gunawan (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2020)
This study aims to measure and analyze the application of the halal concept in tourism attractions of the Tsunami Aceh Museum and the PLTD Floating Ship (Kapal Apung PLTD) sites in the Banda City, Indonesia. It also attempts to assess the contributions of halal tourism to the economy, measured by income multiplier effects. Of 1,243 halal tourism visitors, entrepreneurs surrounding the halal objects, and employees in the halal tourism sites, 93 of them were selected as the sample of the study using the proportionate stratified random sampling technique. Observation, interviews, and questionnaires were used to gather the primary data. Majority of the respondents perceived that the tourist attractions of the Tsunami Aceh Museum and the PLTD Floating Ship had implemented the halal tourism concept. The study also found that those halal tourism objects have contributed to the enhancement of the community's economic development, indicated by the Keynesian Local Income Multiplier and Ratio Income Multiplier of greater than one. To further enhance the community income surrounding the halal tourism objects, the halal tourism facilities should be well-equipped and ensured a conducive surrounding environment.========================================================================================================Bagaimana Kontribusi Pariwisata Halal terhadap Perekonomian Masyarakat? Kajian pada Museum Tsunami dan PLTD Apung Banda Aceh, Indonesia. Penelitian ini bertujuan untuk mengukur dan menganalisis penerapan konsep halal pada objek wisata Museum Tsunami Aceh dan situs Kapal Apung PLTD (Kapal Apung PLTD) di Kota Banda, Indonesia. Penelitian ini juga mencoba untuk menilai kontribusi pariwisata halal bagi perekonomian, diukur dengan efek pengganda pendapatan. Dari 1.243 pengunjung wisata halal, pengusaha di sekitar objek wisata halal, dan tenaga kerja di lokasi wisata halal tersebut, 93 orang di antaranya dipilih sebagai sampel penelitian dengan menggunakan teknik proportate stratified random sampling. Pengamatan, wawancara, dan kuesioner digunakan untuk mengumpulkan data primer. Mayoritas responden menilai tempat wisata Museum Tsunami Aceh dan Kapal Apung PLTD sudah menerapkan konsep wisata halal. Hasil penelitian juga menemukan bahwa obyek wisata halal tersebut telah memberikan kontribusi terhadap peningkatan pembangunan ekonomi masyarakat yang ditunjukkan dengan Keynesian Local Income Multiplier dan Ratio Income Multiplier lebih besar dari satu. Untuk lebih meningkatkan pendapatan masyarakat sekitar obyek wisata halal, maka sarana wisata halal harus dilengkapi dengan baik dan terjaminnya lingkungan sekitar yang kondusif.